India via Trinidad and Canada:: Negotiating Hospitality in Shani Mootoo’s Short Stories - Chakraborty, Chandrima (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2012)
“Out on Main Street” and “The Upside-downness of the World as it Unfolds,” two stories from Shani Mootoo’s 1993 collection, explore how Canada functions as an interface between the Indian diaspora and its originary cultures. The stories play on dominant impulses to assign ethnic belonging based on skin colour, and Jacques Derrida’s reading of the contradictions inherent in (conditional) hospitality can help us tease out the implications of welcome offered to, and perceived by, Mootoo’s misread and racialized Indo-Trinidadian narrators. These stories illuminate how “India” travels from one diaspora (Trinidad) to another (Canada) and how face-to-face urban encounters enable the consolidation of “Indianness” in Canada. More specifically, they shed light on the processes through which diasporic Indians and white Canadians reproduce norms of Indianness and how these norms erase histories and distinctions within the broader Indian diaspora. Ultimately, Mootoo counters the way skin colour is “read” in Vancouver, and the asymmetries of intercultural encounter in these stories stress the need for a historicized and contextualized understanding of the multiplicity of Indian diasporas in Canada.